2017
DOI: 10.1136/bmjopen-2017-018594
|View full text |Cite
|
Sign up to set email alerts
|

InvestigatingBordetella pertussiscolonisation and immunity: protocol for an inpatient controlled human infection model

Abstract: IntroductionWe summarise an ethically approved protocol for the development of an experimental human challenge colonisation model. Globally Bordetella pertussis is one of the leading causes of vaccine-preventable death. Many countries have replaced whole cell vaccines with acellular vaccines over the last 20 years during which pertussis appears to be resurgent in a number of countries in the developed world that boast high immunisation coverage. The acellular vaccine provides relatively short-lived immunity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The findings also suggested that sustained activation of innate and adaptive immune responses by PAMPs and antigen, respectively, for up to 14 days may be required for optimal induction of immunological memory. Finally, our findings have implications for antibiotic treatment of human volunteers exposed to B. pertussis in a human challenge model under development ( 33 ) and provide comfort that treatment with a single oral dose of macrolide antibiotics is an effective means of terminating the infection provided they are administered 1–2 weeks after the intranasal challenge with live B. pertussis .…”
Section: Discussionmentioning
confidence: 79%
“…The findings also suggested that sustained activation of innate and adaptive immune responses by PAMPs and antigen, respectively, for up to 14 days may be required for optimal induction of immunological memory. Finally, our findings have implications for antibiotic treatment of human volunteers exposed to B. pertussis in a human challenge model under development ( 33 ) and provide comfort that treatment with a single oral dose of macrolide antibiotics is an effective means of terminating the infection provided they are administered 1–2 weeks after the intranasal challenge with live B. pertussis .…”
Section: Discussionmentioning
confidence: 79%
“…However, no two challenges will be identical, depending on how the swab is rolled over the unique contours of each pharynx and how the procedure is tolerated. Alternative methods discussed included intranasal injection as in the non-human primate GAS nasopharyngitis model [47] and HIS for other respiratory pathogens [53][54][55][56]. The record of successful and safe induction of experimental pharyngitis in the 1970s was ultimately decisive in choosing the swab method.…”
Section: Discussionmentioning
confidence: 99%
“…Tohama I and Wellcome 28 strains were included in these studies to compare how these strains differ in their interaction with complement components to more recently isolated UK strains and the Dutch isolate B1917 25 , which has been selected for use in a human challenge model 39 . Tohama I, a strain isolated in Japan in the 1950s and widely used in vaccine manufacture, and Wellcome 28 40 , a whole-cell vaccine strain, both do not express the type III secretion system effector Bsp22 41 .…”
Section: Discussionmentioning
confidence: 99%